TAFSIR OTORITARIANISME: NEGOSIASI PENGGUNAAN AYAT DALAM KEPUTUSAN FATWA MUI TENTANG AHMADIYAH PERSPEKTIF ABOU KHALLED EL FADL - Najiburrohman, Najiburrohman; Zulfa, Nailatuz; Basid, Abd. (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2019)
This paper discusses the MUI fatwa on Ahmadiyah. The purpose of this research is to find out MUI's interpretation of religious harmony, as well as to find out the verses used by MUI in its fatwa on Ahmadiyah through the concept of hermeneutics Abou Khaled El Fadl. To answer this problem, the researcher uses the maudhu'i interpretation approach, which is interpreting the verses of the Qur'an not based on the order of the verses, but based on the problem being studied. It means to explain the verses of the Qur'an by referring to one specific subject, namely Ahmadiyya. This research uses a qualitative approach with library research. Data collection techniques are done by quoting, adapting, and analyzing the literature that is relevant to the problem discussed, then reviewing and concluding. The results showed that; through the authoritative hermeneutics of abou khaled el fadl against the MUI fatwa on the misguidance of the Ahmadiyah, there are several assumptions including: first, of the five conditions that require, there are conditions that have not been fulfilled, namely honesty and conference. Second, there are faith-based assumptions that are very dominant in this institution.